Suspended carbon nanowire biosensor for rapid and label-free salmonella detection / Aung Thiha - Aung , Thiha (2020)
Carbon, the building block life, is rapidly becoming the building block of nextgeneration electronics and sensor materials. Of many ways to handle nanocarbon materials, Carbon Microelectromechanical Systems (C-MEMS) emerges as a unique way for top-down fabrication of three-dimensional carbon micro to nanostructures. In this work, the use of C-MEMS techniques in nanowire biosensor fabrication is explored. Two main hindrances in the use of C-MEMS carbon structures for biosensing lie in miniaturization to nanoscale sensor material and inertness of as-fabricated carbon. This dissertation presents ways to overcome these limitations. First, miniaturization to patterned sub-100 nm carbon nanowires was achieved by optimization of ectrospinning properties and integration of electrospinning photoresist polymer with photolithographic pelatterning. Secondly, a microplasma direct writing technique was developed as a novel non-destructive technique for selective surface functionalization of C-MEMS manufactured carbon electrodes. This method uses a simple setup to pattern carboxylic functional groups on the carbon surface at atmospheric conditions. Surface oxygen percentage as high as 27% has been observed. The fabricated suspended carbon nanowires were integrated with microfluidics and immobilized with biomolecular probes for biosensing. Nanowire biosensing was demonstrated by developing an aptamer-based assay that can detect whole-cell Salmonella. The carbon nanowire biosensor used chemiresistive biosensing to achieve rapid detection of the pathogen with high sensitivity and specificity with a detection limit of 10 CFU/mL, which is more sensitive than conventional methods of detecting bacteria.